Rose Cottage - Stewart M. Mary (London, Hodder and Stoughton, 1997)
When Kate Herrick's grandmother asks her to travel down from Scotland to her childhood home in Todhall to retrieve some papers and family mementoes before Rose Cottage is sold, Kate is happy enough to go, but curious as to the changes she may find there. Widowed in. the recent war - this is the summer of 1947 - and comfortably settled now in London, she has come a long way from her humble beginnings in Todhall, and is in some doubt as to how the village will receive her. But Rose Cottage - a tiny thatched dwelling with a tangle of fragrant roses in the garden - is unchanged, and the villagers seem friendly, and delighted to welcome Kate home again. But there is disturbing evidence of a break-in at the cottage, and then her nearest neighbours, three elderly ladies from what the villagers call Witches' Corner', come with tales of night-time prowlers in the cottage garden, and even ghosts . . . Kate's search for explanations leads her into another, more personal quest. And as she explores her own past, she comes to find a place for herself in the present, and the promise of great happiness in the future. Mary Stewart's new novel is a lyrical evocation of rural life in post-war Britain. Gently humorous, warm and perceptive, it will take her millions of devoted readers back into her own enchanted world.